2023
DOI: 10.3390/ijerph20032378
|View full text |Cite
|
Sign up to set email alerts
|

Social Capital and Rural Health for Refugee Communities in Australia

Abstract: Refugee resettlement significantly contributes to Australia’s migration programs, with recent policy directives prioritising rural resettlement. As a result, the cultural diversity of populations of several Australian rural towns has substantially expanded. Newcomers may encounter challenges becoming part of closed social networks and accessing the resources they need for a healthy life in resettlement. However, there are also benefits that stem from positive integration for newcomers and for receiving populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 82 publications
1
13
0
Order By: Relevance
“…Studies in this field have shown the influence of family and friends [ 20 , 21 ], religious institutions [ 4 , 18 , 20 ], and work [ 19 , 22 ] on the everyday life of people in mental health services. Even with other groups, such as refugees [ 25 ], the centrality of social networks is demonstrated. Occupational therapists are recognized as one of the professionals who have the ability to work through and with social networks [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in this field have shown the influence of family and friends [ 20 , 21 ], religious institutions [ 4 , 18 , 20 ], and work [ 19 , 22 ] on the everyday life of people in mental health services. Even with other groups, such as refugees [ 25 ], the centrality of social networks is demonstrated. Occupational therapists are recognized as one of the professionals who have the ability to work through and with social networks [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising; as noted in the Background healthcare can be di cult to access for all members of rural communities. Factors that were recognised as impacting on access, including the size of the rural or regional town or city, a lack of transportation, and the simple availability of health specialist services [13,20,21,29,30,32,34,36,39]. In Germany, Hahn et al [34] reported that the social security system limits access to healthcare and specialists.…”
Section: Access To Servicesmentioning
confidence: 99%
“…In addition, refugees often perceived themselves as outsiders due to language barriers, different cultural beliefs, and their unemployment status. As a consequence of these issues, it was identi ed that improving access to affordable housing within familiar communities, facilitating language support and industry-speci c language training, employment access, and competence level education for children would be bene cial as they encourage healthy lifestyle behaviours and increase feelings of inclusion and belonging, all of which contribute to successful resettlement and encourage access to healthcare [26,28,30,32]. Additionally, to facilitate communication, dissemination of health information, and prevention and selfmanagement of chronic disease, the creation of yers in different languages, the use of SMS messages, the adaptation of governmental messages to the different religious and cultural backgrounds, as well as the use of pictures and audio-visual messages with simple, clear, and concise language, will allow more refugees to be individually informed rather than having to rely on second-hand information from community leaders, friends, family, or staff from service agencies [23,31,35,37,38].…”
Section: Possible Facilitatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Social capital is a concept that refers to resources embedded in social networks and relationships that can be mobilised to achieve specific goals (Mwanri et al, 2023). French sociologist Pierre Bourdieu first introduced the concept of social capital in the 1980s.…”
Section: Literature Review Social Capitalmentioning
confidence: 99%